Ville et région dans les échanges transatlantiques entre géographes de la première moitié du XXe siècle: convergences et diversité des expériences - Robic, Marie-Claire (1998)
CITY AND REGION IN THE TRANSATLANTIC RELATIONS BETWEEN GEOGRAPHERS IN THE EARLY 20TH CENTURY: CONVERGENCE AND DIVERSITY OF EXPERIENCES -The notions of city and region have been linked in geography during the first half of the 20th century. In this process, ideas and words travelled actively in international networks. Taking the case of three notions (nodality, city-region and conurbation), the author analyses some of the ambiguities occuring in the course of these linguistic exchanges. Then she shows that new problems faced geographers from te late 1920s, as they had to account for urbanization and for the growing scale of intra-national interactions. So their discussions about new concepts participate in their effort, both cognitive and pragmatic, for coping with the emerging urban-regional issues. But differences between geographers emphasize the inequal pressure of planning trends from one country to another.